2010
DOI: 10.1111/j.1475-2743.2010.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of properties of Brazilian Haplustalfs with magnetic susceptibility measurements

Abstract: Magnetic susceptibility (χ, mass specific) is useful for easy indirect estimation of other soil properties at a low cost. The aim of this study was to assess the use of χ as measured with an analytical balance for predicting properties with a substantial influence on the management of Typic Haplustalfs in southern Brazil. To achieve this 48 topsoil samples were taken at the intersection points in a rectangular grid of 20 m × 20 m cells, with 38 of these used for calibration and 10 for validation in regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 33 publications
2
49
0
19
Order By: Relevance
“…These two principal components together explained 53 % of the variability of the soil properties in the three segments studied (US, MS, LS). Siqueira et al (2010), when studying the ability of MS to predict some soil properties, found that the first principal component explained 42 % of the variance of the set of soil properties studied, among which MS was the attribute of greatest discriminatory power within the PC1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two principal components together explained 53 % of the variability of the soil properties in the three segments studied (US, MS, LS). Siqueira et al (2010), when studying the ability of MS to predict some soil properties, found that the first principal component explained 42 % of the variance of the set of soil properties studied, among which MS was the attribute of greatest discriminatory power within the PC1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the evaluation of the expected performance of agricultural systems must be improved by the application of quantitative indicators, e.g., the magnetic susceptibility of the soil (Siqueira et al, 2010), which allow objective comparisons and the exact identification of boundaries of landscape segments in the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daniels et al (1971) grande quantidade de amostras, o que dificulta sua utilização tanto pela pesquisa quanto pelo setor produtivo (Siqueira et al, 2010b;Espinar et al, 2011;Sanchez et al, 2012;Xu et al, 2012;Erdős et al, 2013;Matias et al, 2013). Assim, para que a utilização conjunta da classificação numérica e dos modelos de paisagem seja viável, são necessárias técnicas alternativas para quantificar os atributos do solo.…”
Section: Introductionunclassified
“…Pode-se identificar, por meio deste mapeamento, áreas com maior homogeneidade dos atributos dos solos. Segundo Siqueira et al (2010a), a identificação dessas regiões, chamadas áreas de manejo específico, garante a localização de limites mais precisos entre áreas distintas permitindo, assim, que técnicas agronômicas possam ser transferidas com facilidade e economia, para ambientes semelhantes.…”
Section: Introductionunclassified